2015
DOI: 10.1104/pp.15.00732
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Vulnerability to Drought-Induced Embolism by X-Ray Microtomography

Abstract: Hydraulic failure induced by xylem embolism is one of the primary mechanisms of plant dieback during drought. However, many of the methods used to evaluate the vulnerability of different species to drought-induced embolism are indirect and invasive, increasing the possibility that measurement artifacts may occur. Here, we utilize x-ray computed microtomography (microCT) to directly visualize embolism formation in the xylem of living, intact plants with contrasting wood anatomy (Quercus robur, Populus tremula 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
163
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(172 citation statements)
references
References 61 publications
8
163
0
1
Order By: Relevance
“…This process is known as 'air seeding' and is dependent on the structure of bordered pits and pit membranes [99]. The air-seeding hypothesis is supported by experimental evidence from a range of techniques [100,101], correlations between pit membrane structure and vulnerability to embolism [60•, 73], and by direct visualization of embolism spread between conduits [102,103].…”
Section: Drought-induced Embolismmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is known as 'air seeding' and is dependent on the structure of bordered pits and pit membranes [99]. The air-seeding hypothesis is supported by experimental evidence from a range of techniques [100,101], correlations between pit membrane structure and vulnerability to embolism [60•, 73], and by direct visualization of embolism spread between conduits [102,103].…”
Section: Drought-induced Embolismmentioning
confidence: 99%
“…In addition, we have progress in deciphering the role of stored water in stems [10], branches [11], and leaves [12] in keeping trees alive. Technological advances allow us to study in-situ fluid transport dynamics in trees-and also its collapse-at a previously unattainable level of detail [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial advance in recent years has been the use of imaging technology that allows water to be viewed inside intact plants, revealing the location and formation of embolisms inside stems (Brodersen et al, 2013), roots (Cuneo et al, 2016), leaves (Bouche et al, 2016;Brodribb et al, 2016a;Scoffoni et al, 2017), and flowers (Zhang and Brodribb, 2017). These studies have substantially changed our view of xylem cavitation and repair, indicating that cavitation can propagate quickly between plant organs (Skelton et al, 2017) and that air blockages (embolisms) are not repaired rapidly in trees after rewatering (Charrier et al, 2016;Choat et al, 2016). Cavitation is now widely viewed as long-term damage to the water transport system of trees that occurs under significant water stress and that is repaired by the regrowth of new xylem tissue (Brodribb et al, 2010;.…”
mentioning
confidence: 99%
“…Such a design is considered effective, because it is widely assumed that the hydraulic capacity of smaller distal roots is readily repaired upon rewatering via xylem embolism removal (Domec et al, 2006;Jackson et al, 2000). While much work has demonstrated that xylem embolism reduces hydraulic capacity under severe drought stress (Brodribb et al, 2016a(Brodribb et al, , 2016bChoat et al, 2012), its contribution under mild to moderate stress is less clear (Choat et al, 2016;McElrone et al, 2012;Wheeler et al, 2013;Choat et al, 2010;Torres-Ruiz et al, 2015). Work is still needed to resolve the location and sequence of root hydraulic dysfunction under drought and what tissues are involved in each stage of this process, especially under mild stress where fine root hydraulic conductivity (Lp r ) is known to decrease dramatically (Aroca et al, 2012).…”
mentioning
confidence: 99%